2017
DOI: 10.1021/acs.energyfuels.7b00419
|View full text |Cite
|
Sign up to set email alerts
|

Dodecylbenzenesulfonic Acid as a Bitumen Modifier: A Novel Approach To Enhance Rheological Properties of Bitumen

Abstract: Bitumen deterioration has been traditionally overcome by its modification with polymers, sometimes producing unstable blends as a result of their mutual lack of affinity. A new and different approach based on the use of dodecylbenzenesulfonic acid (DBSA) is herein reported. DSBA is a surfactant that contains a strong acid group capable of interacting with asphaltene molecules, commonly used as a dispersing agent for asphaltenes in crude oils. However, the contrary effect can also be obtained, as long as a crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…It means that SDS, as an anionic surfactant, can reduce the π–π interactions between asphaltene molecules, and it can be considered as an asphaltene dispersant. This finding confirms the previous experimental works published in the literature. For CTAB and CAPB surfactants, both dimers and trimers with π–π interactions were observed; however, in the case of TX-100, the configuration of the archipelago architecture is mainly dimers, and for the island architecture, a trimer is dominant (see Supporting Information).…”
Section: Resultssupporting
confidence: 89%
“…It means that SDS, as an anionic surfactant, can reduce the π–π interactions between asphaltene molecules, and it can be considered as an asphaltene dispersant. This finding confirms the previous experimental works published in the literature. For CTAB and CAPB surfactants, both dimers and trimers with π–π interactions were observed; however, in the case of TX-100, the configuration of the archipelago architecture is mainly dimers, and for the island architecture, a trimer is dominant (see Supporting Information).…”
Section: Resultssupporting
confidence: 89%
“…% of dodecyl benzene sulfonic acid (DBSA), the asphaltene precipitation could be completely controlled. Similarly, Ortega et al [10], suggested that the attachment of DBSA to asphaltene molecules with 3 wt % DBSA could noticeably improve the rheological properties of bitumen. Hashmi et al [11] studied the capability of commonly available surfactant aerosol-OT (AOT) to stabilize asphaltene suspensions in heptane.…”
Section: Introductionmentioning
confidence: 88%
“…To date, various modifiers have been employed to obtain the required compatibility and reduce the phase separation during polymer modification of bitumen. Among the most common modifiers: reactive polymers, polyphosphoric acid, organometallic compounds, sulfonic acid, silanes, maleic anhydride, carboxylic anhydride, thiourea dioxide, sulphur, antioxidants, nanomaterials, clay minerals, plasticizers, and bio-oil [ 4 , 105 , 162 , 205 , 210 , 285 , 286 , 287 , 288 , 289 ]. Table 5 lists different the chemical modifiers used for plastomeric bitumen modification.…”
Section: Enhancements Of Plastomer-modified Bitumen Due To Chemical Modifiersmentioning
confidence: 99%